1987
DOI: 10.1002/mrm.1910040409
|View full text |Cite
|
Sign up to set email alerts
|

The effect of moderate blood alcohol levels on T1 and T2 relaxation times in the brains of normal volunteers

Abstract: T1 and T2 measurements of the brains of six human volunteers did not change in the presence of moderate blood alcohol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…There are several possible explanations for the contradictory findings. The peak BAC achieved in the present study ranged from 63 to 97 mg/dl (tissue concentrations: ϳ13.7-21.0 mM), similar to the range of 46 to 99 mg/dl (ϳ10.0 -21.5 mM) reported by Logsdail et al (1987) but considerably lower than the 143 to 197 mg/dl (ϳ31.0 -42.7 mM) attained by Mander et al (1985). Although the latter investigators reported a water proton T 1 decrease of 1% during acute intoxication in normals, it is unclear whether their measurements had adequate statistical power to detect a change this small given their reported T 1 precision of 2.6% and data from only five subjects.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There are several possible explanations for the contradictory findings. The peak BAC achieved in the present study ranged from 63 to 97 mg/dl (tissue concentrations: ϳ13.7-21.0 mM), similar to the range of 46 to 99 mg/dl (ϳ10.0 -21.5 mM) reported by Logsdail et al (1987) but considerably lower than the 143 to 197 mg/dl (ϳ31.0 -42.7 mM) attained by Mander et al (1985). Although the latter investigators reported a water proton T 1 decrease of 1% during acute intoxication in normals, it is unclear whether their measurements had adequate statistical power to detect a change this small given their reported T 1 precision of 2.6% and data from only five subjects.…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with the results of Logsdail et al (1987) but contradicts several other reports (Besson et al, 1981;Hirakawa et al, 1994;Mander et al, 1985;Melgaard, 1983). There are several possible explanations for the contradictory findings.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since the first study demonstrating that T t is increased in chronic alcoholics during the early withdrawal phase and that this is maintained even after the recovery of the acute phase of the illness, several studies have now been carried out that have substantiated these early findings, despite the fact that initially somewhat controversial results were obtained (Smith et al, 1985;Logsdial et al, 1987). Table I summarises the findings of T, and T z changes in response to alcohol administration.…”
Section: Figmentioning
confidence: 98%